The first biography of Jesus genre and meaning in Mark's gospel - Bond, Helen K. 1968- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2020)
"Argues that Mark's author used the genre of biography to extend the gospel from an earlier narrow focus on the death and resurrection of Jesus so that it included the way of life of its founding figure"
Includes bibliographical references and index
Keywords: Jesus Christ -- Biography -- History and criticism; Jesus Christ; Bible -- Criticism, interpretation, etc; Biography as a literary form; Classical biography -- History and criticism